The Effect of Squishy Play Therapy on Reducing Anxiety in Toddlers during Hospitalization - Shelsa Mutiara Sukma; Siti Arifah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hospitalization often triggers anxiety in children, characterized by reactions such as crying, fussiness, and restlessness, which vary among individuals. Play therapy can play an important role in distracting children from the pain or discomfort they experience. This study aims to examine the effect of squishy play therapy on reducing anxiety in toddlers during hospitalization. This was a quasi-experimental study with a one-group pretest-posttest design. This study involved purposive sampling techniques to recruit 15 children. Data were collected using a demographic questionnaire (age, gender, length of stay, and hospitalization history) and the Face Anxiety Scale (FAS). The collection process involved direct observation of anxiety levels before (pre-test) and after (post-test) the squishy play therapy intervention. Data analysis was performed using the Wilcoxon test, with the processing involving editing, coding, scoring, data entry, cleaning, and tabulating. The findings showed that the application of squishy play therapy resulted in a significant reduction in anxiety, with a p-value of 0.001 (p < 0.05). Thus, this intervention is proven to be effective in reducing anxiety in toddlers during hospitalization.This study is expected to contribute to the development of nursing practice through the use of squishy play therapy as an innovative non-pharmacological strategy that can be applied to improve the well-being of children in a hospital setting.